The Impact of Lecturer Talk on EFL Context: Student’s Attitudes in Focus - Ibrahim, Asma; Sakka, Wahyuni; Ruswanti, Reny (Eduvelop: Journal of English Education and Development, 2025)
One of the most important pedagogical tools in English language training is lecture discourse, which has a significant impact on how students approach learning. Having a positive outlook is essential for improving motivation, involvement, and language skills. But nothing is known about how Lecturer Talk could encourage these kinds of views. In addition to identifying efficient communication techniques to improve motivation and engagement, this study explores the effects of Lecturer Talk on students' attitudes towards studying English. 40 students and one lecturer in the management program at STIE Yapman Majene were given questionnaires as part of a mixed-methods approach, which also included video recordings of classroom interactions. The Miles and Huberman framework was used to analyses the qualitative data, and SPSS software was used to evaluate the quantitative data. An analysis of two classroom sessions showed that lecturers' primary topics of conversation during the first session were teaching (30.64%) and giving directions (24.65%), whereas in the second session, the percentage of lecturers giving directions rose to 45.94%. An ANOVA significance value (p < 0.05) corroborated the statistical analysis's finding that lecturer talking and students' attitudes had a substantial positive connection (R = 0.317). Good lecturers encourage positive attitudes and increase students' interest in studying English, especially when they provide clear instructions and use structured teaching methods. This study supports the journal's emphasis on cutting-edge teaching methods by highlighting the crucial role that lecturer discourse plays in influencing students' attitudes and offering practical advice for teachers looking to improve communication techniques in language instruction.